Co-Designed Agile Feed Network for a Polarization Tunable 15 GHz Antenna All-Integrated on Silicon - Corentin Le Lez; Rozenn Allanic; Denis Le Berre; Cedric Quendo; Francois Gallee; Aude Leuliet; Thomas Merlet; Rose-Marie Sauvage; Douglas Silva de Vasconcellos; Virginie Grimal; Jerome Billoue (IEEE Access)
This article presents an all-integrated agile feeding network at 15 GHz enabling the polarization agility of a dual-fed patch antenna, allowing the switching between LHCP (Left Hand Circular Polarized), H-LP (Horizontal Linear Polarized) and V-LP (Vertical Linear Polarized) configurations. Semiconductor Distributed Doped Areas (ScDDAs) are used with an adequate size for the global function optimization and for integrated tunability on a High Resistivity Silicon (HR Si) substrate as variable shunt resistors in the attenuators. Each component of the system has been separately analyzed in small and large signal setups to highlight the relevance of the ScDDAs in this use case. The antenna and its reconfigurable feeding network are designed as a whole in a single process flow. The device allows for an analog control and high polarization contrast interpolating between H-LP, V-LP and LHCP polarizations. The high integrability, low bias voltage, manufacturing simplicity and tuning range of this device without sacrificing the antenna frequency is matching the needs of compacity, agility and robustness of next generation communication and RADAR systems.